Supply Chain Management's Analysis In Improving Nopia Mino Production Using SCOR Model - Apriliana Puspitaningrum; Dwi Mustika Kusumawardani; M Yoka Fathoni (Sistemasi: Jurnal Sistem Informasi, 2022)
Supply chain is an activity to convert raw materials into products that will be marketed to consumers. Besides, Supply Chain Management is a process for efficient integration where goods can be produced and distributed in the right quantity, time, and location between suppliers, factories, distributors, and end customers to minimize costs to provide customer satisfaction. Kampoeng Wisata Nopia Mino is production center for nopia and mino from Banyumas which was established to introducing Banyumas typical snacks and improve economy of local residents. The production of nopia mino has several problems. One is there is competition between fellow makers of nopia mino. Besides, nopia mino production during the pandemic was decreasing. With these problems, it is necessary to measure the production decline that occurred in home industry and develop a production strategy for nopia and mino. Hence, it can maximized in the development of its business. The solution is carried out using the SCOR Model method. The SCOR Model has six processes including plan, source, make, deliver, return, and enable. The results of this study stated that the highest value for large is in the return process of 34 and the lowest value is in the plan process of 11.89, while the highest value for lower is in the make process of -50.5 and the lowest value is in the plan process of -197. Based on the results of these studies, in this study recommendations are given to improve Supply Chain Management in increasing the production of nopia and mino.